(untitled) (Proceedings of Southern Federal University. Philology, 2022)
DOI 10.18522/1995-0640-2022-3-53-61 Throughout the historical development of mankind, regardless of era, religion, race and culture, society is based on one of the fundamental aspects — the institution of marriage and the family. The phenomenon of the family becomes the basis not only for sociological and psychological research, but also finds fictional reflection in the work of modern authors, particularly English-speaking writers. The article describes and analyzes the linguistic means belonging to different levels and functioning for objectivization of the concept “family” as a sociocultural phenomenon, as well as the presentation of the “female” author’s view of the interpretation of the family phenomenon as a social phenomenon from the point of view of the modern female author – Fiona O’Neill. Keywords: concept, fictional discourse, idiostyle, objectivization